Noise of Motor Vehicles at from of Baiturrahman Great Mosque Semarang City - Syaiful Syaiful; Sri Wiwoho Mudjanarko (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2019)
Research done by the field survey data collection a good number of motor vehicles, the number of motorcycles, the number of general passenger cars and goods by measuring the level of noise generated by the modes of transport. The relationship between the noise generated by the distance of sound sources can be displayed as follows: y = 46,286+0,0483x2+0,00065x3+0,00180x4 means a distance of 56,35 meters of 53,26 dBA noise level.